1994
DOI: 10.1021/bc00030a023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a bifunctional fusion enzyme composed of UDP-galactose 4-epimerase and galactose-1-P uridylyltransferase

Abstract: A fusion enzyme consisting of UDP-galactose 4-epimerase and galactose-1-P uridylyltransferase with an intervening Ala3 linker was constructed by in-frame fusion of E. coli gene galT to the 3'-terminus of the E. coli gene galE that had been extended with the coding sequence for three alanine residues, all contained within a high-expression plasmid. The fusion enzyme was expressed in E. coli and purified 24-fold to about 98% homogeneity by chromatography on hydroxylapatite and Q-Sepharose. On the basis of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It was previously shown that differences in the K m values of native enzymes and fusion proteins reflect the presence of specific interactions resulting from the fusion of the enzymes (5,28). A proximity effect or substrate channeling operates in a fusion enzyme and increases the overall catalytic activity of the reaction (4,13,14,26,27,33,35,42). In this process, the reaction product of the first enzyme is transferred directly to the active site of the second enzyme in the sequential enzyme complex or fusion enzyme, without diffusing freely in solution.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that differences in the K m values of native enzymes and fusion proteins reflect the presence of specific interactions resulting from the fusion of the enzymes (5,28). A proximity effect or substrate channeling operates in a fusion enzyme and increases the overall catalytic activity of the reaction (4,13,14,26,27,33,35,42). In this process, the reaction product of the first enzyme is transferred directly to the active site of the second enzyme in the sequential enzyme complex or fusion enzyme, without diffusing freely in solution.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report about a fusion protein composed of UDPGal 4-epimerase and galactose-1-phosphate uridylyltransferase (GalT) with an intervening Ala 3 linker was shown to exist in three forms: a monomer, dimer, or tetramer (20). Another fusion protein of ␤-galactosidase and galactose dehydrogenase was also shown to exist as two major forms, consisting of four or six subunits, as well as other forms (21).…”
Section: Discussionmentioning
confidence: 98%
“…These fusion enzymes change the donor requirement of the ␣1,3GalT from UDP-Gal to UDP-Glc. Furthermore, the fused enzyme system that catalyzes a sequential reaction may also have a kinetic advantage over the mixture of two separated enzymes, since the product of one enzyme travels a shorter distance to be captured by the next enzyme (20,21).…”
mentioning
confidence: 99%
“…Such proximity allows a reaction intermediate to be directly transferred to the active site of the next enzyme in a sequential enzyme complex. By preventing serious diffusion of the intermediate, the reaction rates of whole enzymatic processes could be increased (2,13,22). Recently, we reported that a bifunctional fusion enzyme resulting from fusion between T6P synthase and trehalose 6-phosphatase of E. coli exhibited increased catalytic activity during trehalose synthesis (20).…”
Section: Discussionmentioning
confidence: 99%